THE DEVELOPMENT OF HELL FROM JEWISH TO CHRISTIAN THEOLOGY: a Biblical Guide to Hell and Its Existence - Tanasyah, Yusak (Sekolah Tinggi Teologi Widya Agape dan Perkumpulan Teolog Agama Kristen Indonesia, 2022)
According to the view that is relatively common in the wider Christian culture, heaven and hell basically deserve compensation for the kind of earthly life we lead. Good people go to heaven as a worthy reward for a virtuous life, and bad people go to hell as a just punishment for an immoral life; in that way, the scale of justice is sometimes considered balanced. But almost all Christian theologians regard such a view, however commonly it may be in popular culture, as too simplistic and unsampled; the biblical perspective, as they see it, is much more subtle than that. It is important to acknowledge the polemical and apologetic setting of its development. Judaism underwent modifications to protect the Jewish faith and chastise apostates in the face of invading Hellenism. For the early Christ-movement, continued growth was necessary to defend itself against both internal defection and first-century Judaism and Greco-Roman paganism. The early church fathers believed that using the dread of damnation to uphold moral standards was ideologically motivated. As a result, the evolution of the afterlife may be viewed as a social construct, the effects of which in the contemporary day have had a permanent, harmful influence on many individuals.